Protonatable residues at the cytoplasmic end of transmembrane helix-2 in the signal transducer HtrI control photochemistry and function of sensory rhodopsin I. - Jung, K H (1996)
Neutral residue replacements were made of 21 acidic and basic residues within the N-terminal half of the Halobacterium salinarium signal transducer HtrI [the halobacterial transducer for sensory rhodopsin I (SRI)] by site-specific mutagenesis. The replacements are all within the region of HtrI that we previously concluded from deletion analysis to contain sites of interaction with the phototaxis receptor SRI. Immunoblotting shows plasmid expression of the htrI-sopI operon containing the mutations produces SRI and mutant HtrI in cells at near wild-type levels. Six of the HtrI mutations perturb photochemical kinetics of SRI and one reverses the phototaxis response. Substitution with neutral amino acids of Asp-86, Glu-87, and Glu-108 accelerate, and of Arg-70, Arg-84, and Arg-99 retard, the SRI photocycle. Opposite effects on photocycle rate cancel in double mutants containing one replaced acidic and one replaced basic residue. Laser flash spectroscopy shows the kinetic perturbations are due to alteration of the rate of reprotonation of the retinylidene Schiff base. All of these mutations permit normal attractant and repellent signaling. On the other hand, the substitution of Glu-56 with the isosteric glutamine converts the normally attractant effect of orange light to a repellent signal in vivo at neutral pH (inverted signaling). Low pH corrects the inversion due to Glu-56 -> Gln and the apparent pK of the inversion is increased when arginine is substituted at position 56. The results indicate that the cytoplasmic end of transmembrane helix-2 and the initial part of the cytoplasmic domain contain interaction sites with SRI. To explain these and previous results, we propose a model in which (i) the HtrI region identified here forms part of an electrostatic bonding network that extends through the SRI protein and includes its photoactive site; (ii) alteration of this network by photoisomerization-induced Schiff base deprotonation and reprotonation shifts HtrI between attractant and repellent conformations; and (iii) HtrI mutations and extracellular pH alter the equilibrium ratios of these conformations.